Evaluating the role of aldosterone synthesis on adrenal cell fate - Aminuddin, Amnani; Brown, Morris J.; Azizan, Elena Aisha (Frontiers in Endocrinology, 2024)
Hypertension affects one-third of the adult population worldwide, with primary aldosteronism (PA) accounting for at least 5-10% of these cases. The aldosterone synthase enzyme (CYP11B2) plays a pivotal role in PA manifestation, as increased expression of CYP11B2 leads to excess aldosterone synthesis. Physiological expression of CYP11B2 in humans is normally limited to cells of the adrenal zona glomerulosa under tight homeostatic regulation. In PA, however, there are CYP11B2-positive lesions in the adrenal cortex that autonomously secrete aldosterone, highlighting the dysregulation of adrenal cortex zonation and function as a key aspect of PA pathogenesis. Thus, this review aims to summarize the development of the adrenal glands, the key regulators of adrenal cortex homeostasis, and the dysregulation of this homeostasis. It also discusses the development of CYP11B2 inhibitors for therapeutic use in patients with hypertension, as well as the current knowledge of the effects of CYP11B2 inhibition on adrenal cortex homeostasis and cell fate. Understanding the control of adrenal cell fate may offer valuable insights into both the pathogenesis of PA and the development of alternative treatment approaches for PA.